From Assimilation to Pluralism and Multiculturalism Policy:State Policy Towards Ethnic Chinese in Indonesia (History Department, Semarang State University and Historian Society of Indonesia, 2019)
Indonesian society inherits plural society of Dutch colonization. One of the major problems is related to the minority ethnicity and its position towards the majority. One of the ethnicities which receives special attention from the government is Chinese. This article is trying to analyse the history of Indonesia Government Policy from Indonesian Independence to Reformasi. The results show that from Indonesian Independence to The New Order era, discrimination politics to Chinese in Indonesia occurs. Chinese is trying to create their image being Indonesian by imitating the majorityâ€™s cultural identity or practicing assimilation based on the location where they live. After Reformasi in 1998, the state politics changed by respecting cultures or multicultural society. Therefore, some Chinese identities start to strengthen, but most of them still follow the majority culture.Â Masyarakat Indonesia mewarisi masyarakat majemuk penjajahan Belanda. Salah satu masalah utama terkait dengan etnis minoritas dan posisinya terhadap mayoritas. Salah satu etnis yang mendapat perhatian khusus dari pemerintah adalah Cina. Artikel ini mencoba menganalisis sejarah Kebijakan Pemerintah Indonesia dari era Kemerdekaan Indonesia hingga Reformasi. Hasil penelitian menunjukkan bahwa dari kemerdekaan Indonesia ke era Orde Baru, terjadi diskriminasi politik terhadap Tionghoa di Indonesia. Orang Tionghoa mencoba membuat citra mereka menjadi orang Indonesia dengan meniru identitas budaya mayoritas atau mempraktikkan asimilasi berdasarkan lokasi tempat mereka tinggal. Setelah era reformasi pada tahun 1998, politik negara berubah dengan menghormati budaya atau masyarakat multikultural. Oleh karena itu, beberapa identitas Cina mulai menguat, tetapi kebanyakan dari mereka masih mengikuti budaya mayoritas.Â